2007
DOI: 10.1124/jpet.107.123307
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of α-Aminoazaheterocycle-Methylglyoxal Adducts as a New Class of High-Affinity Inhibitors of Cystic Fibrosis Transmembrane Conductance Regulator Chloride Channels

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) represents the main Cl Ϫ channel in the apical membrane of epithelial cells for cAMP-dependent Cl Ϫ secretion. Here we report on the synthesis and screening of a small library of nontoxic ␣-aminoazaheterocycle-methylglyoxal adducts, inhibitors of wild-type (WT) CFTR and G551D-, G1349D-, and F508del-CFTR Cl Ϫ channels. In whole-cell patch-clamp experiments of Chinese hamster ovary (CHO) cells expressing WT-CFTR, we recorded rapid and reversible inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 41 publications
1
29
1
Order By: Relevance
“…The cell viability of HeLa-F508del-CFTR cells exposed to different concentrations of compounds was evaluated using the mitochondrial-dependent reduction of MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide; Sigma-Aldrich] colorimetric assay, as described elsewhere (Routaboul et al, 2007). Cells were incubated at 37°C with the test compound at the concentration and time of incubation previously defined.…”
Section: Methodsmentioning
confidence: 99%
“…The cell viability of HeLa-F508del-CFTR cells exposed to different concentrations of compounds was evaluated using the mitochondrial-dependent reduction of MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide; Sigma-Aldrich] colorimetric assay, as described elsewhere (Routaboul et al, 2007). Cells were incubated at 37°C with the test compound at the concentration and time of incubation previously defined.…”
Section: Methodsmentioning
confidence: 99%
“…Similar experiments were performed with the minor isomer GPact-11b leading to an EC50 of 2.9¡0.9 mM (data not shown, n54). The effect of GPact-11a was fully inhibited by CFTR inh -172, GlyH-101 and GPinh-5a, three selective CFTR inhibitors [13,26,27] but was not affected by DIDS and calixarene, two non-CFTR inhibitors [28] (fig. 1e).…”
Section: Effect Of Gpact-11a On Wt-cftr Activitymentioning
confidence: 99%
“…GPinh-5a was synthesised as previously described [13]. Miglustat was from Toronto research chemicals (Toronto, ON, Canada).…”
Section: Other Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The glycine hydrazides block the CFTR pore at its external surface, which allowed the synthesis of nonabsorbable polyethylene glycol and lectin adducts that do not cross membranes and block intestinal fluid secre-tion in animals models of cholera (Sonawane et al, 2006(Sonawane et al, , 2007. Routaboul et al (2007) recently reported that ␣-aminoazaheterocyclic-methylglyoxal adducts inhibit CFTR chloride channel function completely and reversibly, with low picomolar IC 50 values, more than 10,000-fold better than the most potent known CFTR inhibitors. The picomolar-potency compounds were identified by screening a collection of seven ␣-aminoazaheterocyclic-methylglyoxal adducts.…”
mentioning
confidence: 99%